Cryogenic landforms in the Sierras de Alvear, Fuegian Andes, subantarctic Argentina - Valcárcel Díaz, M.; Carrera Gómez, P.; Coronato, Andrea Maria Josefa; Castillo Rodríguez, F.; Rabassa, Jorge Oscar; Pérez Alberti, A. (Permafrost and Periglacial Processes)
A preliminary survey of periglacial landforms found in the Monte Alvear region of the Fuegian Andes, subantarctic Argentina has revealed the presence of nivation hollows, subnival 'boulder' (clast) pavements, protalus ramparts, debris lobes, patterned ground and cryo-ejected clasts. With the exception of debris lobes and cryo-ejected clasts, all the landforms show some degree of activity and are, therefore, considered as indicators of present-day cryonival morphodynamics at higher elevations in these mountains. A number of small tors, while not necessarily periglacial in origin, are also apparently experiencing cryogenic weathering. Fil: Valcárcel Díaz, M. Universidad de Santiago de Compostela; España Fil: Carrera Gómez, P. Universidad de Santiago de Compostela; España Fil: Coronato, Andrea Maria Josefa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Castillo Rodríguez, F. Universidad de Santiago de Compostela; España Fil: Rabassa, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Pérez Alberti, A. Universidad de Santiago de Compostela; España